Effect of educational multimedia on anxiety before cesarean section - Zeinab Rabiei; Faezeh Jahanpour; Farzan Azodi; Parviz Azodi (Mashhad University of Medical Sciences, 2017)
Introduction: Most people experience some degree of anxiety before surgery that when it increased can cause serious complications. This study was performed with aim to evaluate the effect of educational multimedia on preoperative anxiety in patients undergoing cesarean section in Bushehr University of Medical Sciences. Methods: This single-blind clinical trial was performed on 162 patients aged 16 to 50 years referred to the educational hospitals of Bushehr for elective cesarean section in 2014. The subjects were assigned to experimental and control groups. One night before the surgery, the experimental group was given a VCD (containing educational videos related to surgery and various types of anesthetics) and was shown by the researcher. The control group received no intervention. Amsterdam questionnaire was used to assess preoperative anxiety. Data was analyzed by SPSS software (version 19) and t-test and ANOVA. P<0.05 was considered significant. Results: The mean score of total anxiety in the control group was 21.92±4.99 and in the experimental group was 17.44±5.88, and the difference was statistically significant (p<0.05). No significant relationship was observed between anxiety score in both groups and demographic factors of the samples. Conclusion: The use of educational multi-media is effective to reduce the patient's anxiety before surgery; therefore it is recommended to be used in patients before surgery.